Hubungan Usia, Jenis Kelamin, Dan Pekerjaan Dengan Kejadian Dermatofitosis di Rumah Sakit Umum Daerah Dr. H. Abdul Moeloek Provinsi Lampung Periode 2017- 2021 - Graceciela, Yohana Eva; Anggraini, Dwi Indria; Himayani, Rani; Sibero, Hendra Tarigan (CV. Jasa Sukses Abadi, 2024)
Dermatophytosis is a dermatophyte fungal infection that attacks keratinized tissues. This disease can be caused by various internal and external factors. The internal risk factors causing dermatophytosis include age, gender, and occupation. In addition to that, this study aimed at determining the relationship between age, gender, and occupation toward dermatophytosis cases. This study used an analytical observational design with a cross-sectional approach. The sample in this study consisted of 114 patients with dermatophytosis sourced from the secondary data in the form of medical records. The research data were conducted by using total sampling technique in RSUD Dr. H. Abdul Moeloek Lampung Province. The recorded data included the patients’ age, gender, occupational, and diagnosis. Then, the data were analysed using chi-square test presented in tabular form. The results showed that the majority of dermatophytosis patients were adults, female, and employees who worked in government/private institutions. The results of the chi-square test showed a significant value for the age variable (p = 0.035) and the gender variable (p = 0.041), while for the work variable there was no significant relationship (p = 0.615). There is a significant relationship between age and gender with the dermatophytosis cases and there is no significant relationship between occupation and the dermatophytosis cases.